Answer:
Right option is B. x = -3 ± 2√5
Explanation:
Given equation,
x² + 6x - 11 = 0
Using quadratic formula,
![x = \frac{-b ± \sqrt{b^(2) -4ac}}{2a}](https://img.qammunity.org/2020/formulas/mathematics/high-school/pc4g01m0sqjsloh76infw5hs22undbu9ai.png)
Comparing from general quadratic equation: ax² + bx + c = 0
Here, a= 1 b = 6 and c = -11
so,
![x = \frac{-6 ± \sqrt{6^(2) -4·1·(-11)}}{2·1}](https://img.qammunity.org/2020/formulas/mathematics/high-school/8suerxbsxioxd5sxh3exrgb5uo7hmklbav.png)
![x = (-6 ± √(36 +44))/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/xrtssf1yrqsvftuogdnv9tbkhj4wod1uc8.png)
![x = (-6 ± √(80))/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/d6jjb22hrvzccn41xgree7l4ahxvdyvaz2.png)
x = -3 ± 2√5
Hence right option is B. x = -3 ± 2√5